2018
DOI: 10.1175/jtech-d-17-0144.1
|View full text |Cite
|
Sign up to set email alerts
|

A Performance Evaluation of the World Wide Lightning Location Network (WWLLN) over the Tibetan Plateau

Abstract: A systematic evaluation of the performance of the World Wide Lightning Location Network (WWLLN) over the Tibetan Plateau is conducted using data from the Cloud-to-Ground Lightning Location System (CGLLS) developed by the State Grid Corporation of China for 2013–15 and lightning data from the satellite-based Tropical Rainfall Measuring Mission (TRMM) Lightning Imaging Sensor (LIS) for 2014–15. The average spatial location separation magnitudes in the midsouthern Tibetan Plateau (MSTP) region between matched WWL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 32 publications
2
30
1
Order By: Relevance
“…In both the PV and TC thunderstorms, the system developed from east to west, and both were dominated by negative CG lightning; this agrees with Fan et al (2018), who found that the proportion of positive CG lightning in the eastern part of the QTP is low. The liquid water content and convective activities within the clouds have a key influence on the initiating discharge process, and the cold cloud regions (TBB < −40 °C) and the regions with a large TBB gradient are more favorable to the development of CG lightning, which is consistent with the analysis of strong thunderstorm weather in Hohhot (Li et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…In both the PV and TC thunderstorms, the system developed from east to west, and both were dominated by negative CG lightning; this agrees with Fan et al (2018), who found that the proportion of positive CG lightning in the eastern part of the QTP is low. The liquid water content and convective activities within the clouds have a key influence on the initiating discharge process, and the cold cloud regions (TBB < −40 °C) and the regions with a large TBB gradient are more favorable to the development of CG lightning, which is consistent with the analysis of strong thunderstorm weather in Hohhot (Li et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…A CG lightning strike consists of one to multiple strokes within a specified time and distance. As a result, a strike is defined as a set of strokes sequentially separated in time by no more than 0.5 s and in space by no more than 10 km (Zheng et al ., 2016a; Zheng et al ., 2016b; Fan et al ., 2018). For the LS‐scheme, a definition method similar to that of Ukkonen and Mäkelä (2019) was adopted.…”
Section: Data Processing and Methodsmentioning
confidence: 99%
“…Then, the user workstation processes or issues lightning information. The lightning information for a certain period is the CG lightning detection data, which include the precise occurrence time, latitude, longitude, polarity and peak current of any single lightning strike (Fan et al ., 2018).…”
Section: Study Area and Datamentioning
confidence: 99%
“…Therefore, the WWLLN strokes were grouped into flashes in this study to analyze the corresponding flash activities. The grouping algorithm is based on time and space criteria of 0.5 s and 30 km, respectively [66]. Here, a "WWLLN flash" is a collection of strokes that occur near each other in time and space and are not necessarily part of the same lightning flash.…”
Section: Wwllnmentioning
confidence: 99%